Involvement of the Actin Machinery in Programmed Cell Death - Ren, Weida; Zhao, Wanyu; Cao, Lingbo; Huang, Junqi (Frontiers in Cell and Developmental Biology, 2021)
Programmed cell death (PCD) depicts a genetically encoded and an orderly mode of cellular mortality. When triggered by internal or external stimuli, cells initiate PCDs through evolutionary conserved regulatory mechanisms. Actin, as a multifunctional cytoskeleton protein that forms microfilament, its integrity and dynamics are essential for a variety of cellular processes (e.g., morphogenesis, membrane blebbing and intracellular transport). Decades of work have broadened our knowledge about different types of PCDs and their distinguished signaling pathways. However, an ever-increasing pool of evidences indicate that the delicate relationship between PCDs and the actin cytoskeleton is beginning to be elucidated. The purpose of this article is to review the current understanding of the relationships between different PCDs and the actin machineries (actin, actin-binding proteins and proteins involved in different actin signaling pathways), in hope that this attempt can shed light on ensuing studies and the development of new therapeutic strategies.